A young female with hypocomplementemic urticarial vasculitis associated with a rare CNS manifestation. Issue 2 (April 2023) - , Safi Alqatari; , Manal Hasan; , Raed Bukhari Fatimah Alabdrabalnabi; Hadhiah, Kawther; , Fatimah Al Ohaid; , Abrar Alwaheed; Aldarwish, Abdullah W
No abstract available